(untitled) (Journal of Contemporary Philology, 2023)
The paper deals with the multifunctionality of the particle ajde in the Macedonan colloquial language. This Turkish loan is deeply rooted in all Balkan languages where it performs a wide range of functions in everyday oral communication. In spite of its undisputed status of a Balkanism it remains an understudied subject in typological literature. To explore the communicative potential of ajde we conducted an analysis of its discourse functions in various speech acts using a sample of collected examples from fiction works and telephone conversations. We suggest that the multifunctionality of ajde can be attributed to its contextual dependency: the original hortative meaning of ajde accommodates to the illocutionary force of the speech act it prefaces whereby acquiring properies characteristic of interpersonal discourse markers. Ajde acts as a hedge in directives but as a booster in commissives and expressives. The opposing fucnctions of ajde can be accounted for by its ability to operate in strategies involving positive politeness, a frame so characteristic of Balkan languages.